Attitudes towards Rape and Societal Stigmatization of the Victims - Khanal, Archana (Patan Pragya, 2022)
Despite the fact that the globe is working tirelessly to advocate for women's rights, Nepali society's attitude toward violence against women (VAW) remains unchanged. This article is based on study conducted with forty- two respondents from Kathmandu valley. The study assesses the status of the victims, attitudes towards rape, rape myths, and social stigmatization between respondent groups: victims and community people. Ten victims sheltered in NGO, thirty community people were administered questionnaire and collected quantitative data and two key informants working in this sector were interviewed and collected qualitative data. Most of the victims in this study were raped during their adolescence and twenty percent among them were re-victimized but none of them filed complaint due to fear of staining family prestige. All of the victims had to stay away from their families either temporarily or permanently. Ninety percent have faced stigma. Substance abuse and sexual gratification were listed as the main causes of rape by both group victims and the community people. No Strict Adherence to existing laws and political protection to powerful/wealthy perpetrators were the main shortcomings of the law.